Exposure duration and composition are important variables to predict short-term toxicity of effluents to a tropical copepod, Acartia sinjiensis. (15th May 2022) - Stone, Sarah; McKnight, Kitty S.; Naab, Christoph; Koppel, Darren J.; Binet, Monique T.; Jolley, Dianne F.; Simpson, Stuart L.
Abstract: Predicting the toxicity of effluent exposures, which vary in duration, composition, and concentration, poses a challenge for ecological risk assessments. Effluent discharges may frequently result in the exposure of aquatic organisms to high concentrations of mixed contaminants for short durations. In the receiving environment effluents will undergo dilution and physical or chemical processes that further reduce contaminant concentrations at varying rates. To date, most studies comparing toxicity risks of continuous and pulsed contaminant exposures have focused on individual contaminants. In this study, the toxicity to the tropical euryhaline copepod Acartia sinjiensis of two complex effluents was assessed, comparing 6- and 18-h pulses and 78-h continuous exposures. Observations of larval development success and population size were completed after a 78-h incubation period, to observe for latent effects after pulse exposures. The chemical compositions of the effluents were assessed over time and different contaminants (i.e., metals, ammonia or organics) declined at differing rates. These were characterized as either a minimal, steady, or rapid decline. Nauplii development and population after 78 h were more impacted by effluent exposures following an 18-h pulse, compared to a 6-h pulse. Based on pulse-exposure concentrations, the 50% effect concentrations (EC50) were similar for continuous and 18-h exposures but up to 3-fold greater (lower toxicity) for the shorter 6-h exposures. Time-weighted average concentrations did not accurately predict toxicity from pulse exposures of the effluents. Concentration-addition toxicity modelling using toxicity data from pulse exposures of single contaminants was useful for predicting the toxicity of chemical mixtures exposed for varying durations. Recommendations for modified approaches to assessing risks of short-term effluent discharges are discussed. Graphical abstract: Image 1 Highlights: Toxicity of complex effluents increased slightly with increasing 6–78 h duration. Nauplii were more sensitive to an 18-h and 78-h exposures compared to 6-h exposure. Time-weighted average concentrations were not suitable for predicting mixture toxicity. Continuous exposures provided conservative toxicity estimates for pulse exposures. Concentration-addition models provided useful prediction of mixture pulse toxicity.